Measurement reliability and effect of hip strengthening exercises in knee osteoarthritis. - Sled EA (Measurement Reliability & Effect of Hip Strengthening Exercises in Knee Osteoarthritis, 2008)
The progression of knee osteoarthritis (OA), the most common cause of physical disability in older adults, is influenced by muscular and biomechanical factors. Reliability of muscular and biomechanical measures, including knee muscle strength and limb alignment, is critical. Furthermore, conservative interventions that slow the course of OA disease progression and prevent disability are urgently needed. The objectives of this thesis were to: (1) investigate the reliability of measures of knee muscle strength and alignment in persons with knee OA, and (2) determine the influence of an exercise intervention targeting hip muscles on knee joint loading in those with medial knee OA.In the first study reliability of knee muscle strength measures was evaluated within one testing session in 40 persons with knee OA. Isometric and isokinetic peak torque values for the quadriceps and hamstring muscles demonstrated high degrees of intra-session reliability.Reliability of lower limb alignment measures was determined following a bone landmark-based approach with use of a computer program. Excellent reliability coefficients were found which compared favorably with reliability of manual measures from schematics of limb deformities drawn with AutoCADRTM software. When the computer method was applied to 100 full-limb radiographs of persons with or at risk for knee OA, alignment measures demonstrated high inter- and intra-reader reliability.Hip muscle weakness may influence loading of the medial knee compartment. Hip abductor strength was evaluated in 40 individuals with medial compartment knee OA in comparison to a control group of 40 healthy older adults. The effect of an 8-week home-based hip abductor strengthening program on the knee adduction moment was also assessed in this group with knee OA, compared with the control group which received no intervention. Following the exercise program the OA group demonstrated improvements in hip abductor strength and functional performance on a sit-to-stand task. There were no changes in the knee adduction moment. Thus, hip muscle strengthening did not influence joint loading, but may improve function in persons with knee OA.Results from this thesis provide increased understanding of knee OA, from muscular and biomechanical perspectives, in the areas of measurement reliability and exercise intervention.